A repercussão geral no processo penal democrático e o prejuízo à recorribilidade - Santos, Liziane dos (2014)
The present paper had been produced in concentration area of Penal System and Violence, at Research Line on Contemporaneous Juridical Penal Systems, throughout analysis of legislation, doctrine and Jurisprudence about the admissibility requisite of General Repercussion as known, preliminary at extraordinary appeals on criminal matter ambit premise which was included into juridical ordinance herein have been starting from number 45 Constitutional Amendment, of 2004, December 30th. During research, it did search for investigate all over adequacy of such a requirement from Law and Penal Process, detaining special attention on those terms contained at text of 543-A and 543-B articles from Civil Process Code, than ruptures with an appellate-equalized paradigm between Penal and Civil processes in face of the inherent warranties for a democratic Penal Process. Had whilst gone into considerations around damages to Penal Process inherent to fragility of adopted criteria at election of hypothesis which would have configure General Repercussion, including the form of judgment for Relevance Allegement that occurs through institution of a Virtual Tribunal, created and developed in the year of 2007− with objective of concentrating discussions about having existence or not regarding to General Repercussion on Constitutional questions sustained through Extraordinary Appeals, wherein the result of judgment is thrown in an automatic and electronic mode. It had pondered, finally, that Penal Law as well as Penal Process, do count with proper principles and guarantees from a system which must be rescued from way to guarantee the presuppositions of a Penal Process materially Democratic. At dissertation development, incursions happened emphasizing superiority of values notion, finalities, principles of Penal Process Law, specially, enrolled them at Federal Constitution, without disregarding on necessity of a critical attitude in relation to use of analogy on applied Civil Laws to Penal Process Law. Thus, it had aimed to discuss whether requirement of General Repercussion is in conformity to the demands from a Democratic State of Rights and a Penal Process oriented by guarantees foreseen at Constitutional text, mostly, those ones from Federal Constitution in its article 5th.